Mesenchymal Stromal Cells in Pediatric Hematopoietic Cell Transplantation a Review and a Pilot Study in Children Treated With Decidua Stromal Cells for Acute Graft-versus-Host Disease - Ringdén, Olle; Gustafsson, Britt; Sadeghi, Behnam (Frontiers in Immunology, 2020)
Mesenchymal stromal cells (MSCs) are rare precursors in all organs of the body. MSCs have profound anti-inflammatory effects and reduce alloreactivity in vitro and in vivo. In pediatric allogeneic hematopoietic cell transplantation (HCT), MSCs have mainly been used to treat acute graft-versus-host disease (GVHD). MSCs are commercially available for this indication in Canada, Japan and New Zeeland. More rare indications for MSCs in pediatric patients include graft failure and chronic GVHD. MSCs from bone marrow, adipose tissue, umbilical cord, Wharton’s jelly, placenta tissue and decidua have been used, but the optimal clinical stromal cell source has not been compared in clinical trials. More experimental clinical indications using MSCs, such as sepsis, acute respiratory distress syndrome, hemorrhages, pneumo-mediastinum and neuroinflammation have primarily been explored in animal models or adult HCT patients. MSCs have almost no if any side-effects. In this pilot study we report the outcome of six children treated with decidua stromal cells (DSCs) for steroid refractory acute GVHD. At six months, complete response was seen in four patients and partial response in two patients. One child with high-risk ALL died from relapse and a boy with sickle cell disease died from a cerebral hemorrhage. Five-year survival was 67% and all survivors showed a Lansky score of 100%. To conclude, MSCs from various organs are well tolerated and have shown an encouraging outcome for acute GVHD in pediatric patients.